Quels espaces pour des écritures créatives numériques ? - Luc Dall’Armellina (Éducation et Socialisation)
Schools pushed the creative and sensitive training of pupils and students to inconsistently invested margins. The increasing scarcity of artist-supervised artistic practices (in which artists are school partners), the manipulation of school-objectified arts (which waver between skill and knowledge), and the unsuitability of both places of practice and assessments are all contributors to the denaturation of arts and their virtues. Digital and creative writing will here be discussed in connection with the unsuitable places and modes of practice at schools and universities. Training free and creative subjects is major political challenge for "skholè".